STANDARD OPERATING PROCEDURES AS A STRATEGIC TOOL FOR SERVICE QUALITY MANAGEMENT: A CASE STUDY OF HOUSEKEEPING OPERATIONS IN AN INTERNATIONAL FIVE-STAR HOTEL - Nisfia Salsabilla Putri; Dani Adiatma; Stanny Dhamayanty (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the role of Standard Operating Procedures (SOP) as a strategic tool for service quality management within housekeeping operations in an international five-star hotel. The research employs a descriptive qualitative approach based on direct observation and semi-structured interviews conducted during a one-year on-the-job training period. Data were analyzed through thematic categorization to identify patterns related to SOP compliance, supervisory control, workflow structuring, and quality assurance mechanisms. The findings indicate that structured SOP implementation enhances operational consistency, minimizes service variability, and strengthens preventive quality control systems. Supervisory inspections, checklist-based monitoring, and interdepartmental coordination contribute significantly to service reliability and guest satisfaction. Furthermore, SOP functions not only as an operational guideline but also as a strategic risk management mechanism in maintaining service excellence. This study highlights the strategic contribution of housekeeping operations to overall hotel competitiveness and reinforces the importance of standardized procedures in achieving sustainable service quality.